Cardinal in my window with a mask on its beak - Aguasaco, Carlos (University of Arizona Press, 2022)
"This is the poetry of an American by choice, the insightful voice of a first-generation immigrant to the United States. It is a journey both fantastical and real, revealing shocking and necessary insights into humanity while establishing a transatlantic dialogue with the great voices of the Spanish Renaissance. Cardinal in my Window with a Mask on its Beak's lyrical voice travels a trajectory of social-justice-based poetic portraits of historical migrants such as Ota Benga, Sarah Baartman, Isidro Marcelino Orbés, Cesar Vallejo, and Gertrude Stein among others. With a raw, unapologetic voice, the book leads the readers to question their role in today's society. Moreover, these verses force the reader to examine what it means to have social justice in this, our globalized world, as they confront us with our treatment of the Other, be that the immigrant or the indigenous person or anyone embodying Otherness. Author Carlos Aguasaco embraces his trans-border/trans-national/intercultural identity building a transatlantic bridge across time and distance uniting the great voices of the Renaissance with his lyrical chant and dialogue with Spanish authors such as Juan Boscán, Francisco de Quevedo, Garcilaso de la Vega, and Sor Juana Inés de la Cruz. The resurgence of this new spirit of the Renaissance is incarnated by this poetry that examines the fundamental liberties inherent in humankind. This quest for freedom leads the poetic voice to openly criticize the treatment of immigrants in the United States. For example, one poem addresses the caged immigrant children along the US-Mexico border in parallel depiction of the inhumane treatment of African Ota Benga"--